Neuromuscular adaptations to strength and concurrent training in elderly men. DOI: http://dx.doi.org/10.5007/1980-0037.2012v14n4p483 - Luiz Fernando Martins Kruel; Ronei Silveira Pinto; Eduardo Lusa Cadore (Revista Brasileira de Cineantropometria e Desempenho Humano, 2012)
DOI: http://dx.doi.org/10.5007/1980-0037.2012v14n4p483This paper aimed to review the results of studies on neuromuscular adaptations to strength training (ST) and concurrent training (CT) in elderly men. A literature search was conducted using PubMed, Scopus, and SciELO. The search was limited to studies published from 1980 to 2012. A total of 3,390 articles were retrieved. After reading their titles, 127 studies were further evaluated by reading their abstracts. This resulted in 92 papers that were read in full; 25 of these were selected and their results were described in the present review. Several studies showed that, in elderly subjects, ST can produce increases in muscle strength, power, activation and mass. ST-induced strength gain may be explained by neural and morphological adaptations. The main neural adaptations to ST included increased recruitment of motor units and increased motor unit firing rate. Morphological adaptations included increases in the physiological cross-sectional area (CSA) of the muscle, in muscle thickness, in muscle fiber pennation angle, and changes in muscle myosin heavy-chain isoforms, resulting in the conversion of muscle fiber from subtype IIx to IIa. The inclusion of moderate-to-high inten- sity (60-85% of maximum strength) ST in the routine of this population is recommended to improve neuromuscular function. CT can promote significant neuromuscular adaptations, but these gains may be of a lower magnitude than those obtained with ST. Although CT has an interference effect on neuromuscular adaptations, it also promotes improvement in cardiovascular function and is therefore the most frequently recommended intervention for health promotion in the elderly.